β-Cell function in type 1 diabetes may not be as low as presumed - Gonca, Tamer; Burcu, Dogan; Ozge, Telci Caklili (Journal of Endocrinology And Hormones, 2018)
Objective We aimed to evaluate β-cell function of type 1 diabetic patients (T1DP)s based on fasting and stimulated C-peptide levels. Material and methods Study included 135 T1DPs and 31 healthy subjects. Fasting C-peptide levels were measured in healthy subjects and T1DPs. The Mixed-meal tolerance test (MMTT) was performed in T1DPs. Fasting and stimulated (90 minute post MMTT) C-peptide levels were measured via electrochemiluminescence assay. Two categorizations were made according to fasting (the first categorization ) and at 90th minute MMTT (the second categorization) C-peptide levels. For the first categorization; the groups were classified as follows: patients with undetectable ≤0.1ng/mL(group1); minimal 0.1-0.8ng/mL(group2); and sustained ≥0.8ng/mL (group3) C-peptide levels. For the second categorization, groups were as follows: patients with undetectable ≤0.1 ng/mL(group1); minimal 0.1-0.8 ng/ml (group2); and sustained ≥0.8ng/mL (group3) in which C peptide levels were increased to ≥150% of fasting C-peptide levels at the 90th minute after MMTT. Results For the first category; 41.5%, 40% and 18.5% of T1DPs were in group1, group2 and group3, respectively. For the second category; 34.8%, 20.7% and 44.4% were in group1, group2 and group3, respectively. In first categorization 58.5% and in second categorization 65.1% of T1DPs had detectable C-peptide levels. 44,4%of the T1DPs had a response to MMTT with C-peptide levels ≥0.8 ng/mL which increased to ≥150% of fasting C-peptide level at the 90th minute after MMTT as it is seen in non-diabetics. Conclusion The present study suggests the presence of functioning β-cells in T1DPs and 44.4 % of T1DPs have a response to MMTT as seen in non-diabetics. (ClinicalTrials.gov number: NCT02199470.)
Keywords: β-Cell function; type 1 diabetes; mixed-meal tolerance test.